The atypical Gaoligong orocline: Its geodynamic origin and evolution - Chiu, Yu-Ping; Yeh, Meng-Wan; Lee, Tung-Yi (Frontiers in Earth Science, 2023)
Various orocline systems around the India–Eurasia collision zone have long been recognized and studied. Different portions of the India–Eurasia boundaries represent various scales and models of orocline-forming processes, such as the Baluchistan orocline formed by multiple deformation events and the Himalayan orocline formed by a mixture of complex structural mechanisms. The curvature from the eastern Himalayan syntaxis through east Burma to west Yunnan showed a unique convex curvature toward the mantle wedge. This is different from the concave Baluchistan orocline and the Himalayan orocline. The unique geometry of the Gaoligong orocline shows an N-S trend for the northern section and a NE-SW trend for the southern section. This curvature also marks the boundary between the Tengchong and Baoshan blocks along the Santaishan suture in western Yunnan, China. Our structural reconstruction identified five deformation events: 1) D1 is km-scale upright folding, which only affected the Neoproterozoic meta-sedimentary unit, 2) D2 recumbent folding, which only developed in the southern section of the Gaoligong orocline, 3) D3 large-scale gently westward-inclined thrust folding, 4) D4 right-lateral shear belt, and 5) the D5 normal faults. Since the D3 structure is the earliest event that shows penetrative foliation development along the orocline, we consider D1 and D2 as pre-orocline-forming events. The geometry of the Gaoligong orocline is controlled by the distribution of the Ordovician basement between the Tengchong and Baoshan blocks. Both north and south sections experienced the same structural evolution since D3 (a fault-propagation fold system occurred between 40 Ma and 28 Ma), D4 (steep right-lateral shear belt occurred between 28 Ma and 15 Ma), and D5 (normal faults after 15 Ma). The curvature first developed as a shovel-like top-to-the-NE thrust plane (S3) that formed under amphibolite-facies conditions between 40 Ma and 28 Ma. The following deformation events (D4 and D5) show orocline parallel foliation development under lower metamorphic conditions, indicating that the curvature of the Gaoligong orocline is not generated by additional rotation along multiple deformation events. However, due to the lack of orocline parallel foliation development for S3, and the lack of a proper position of the indenter, the Gaoligong orocline cannot be classified as a primary orocline nor a rotational orocline. The curved geometry is an interference pattern of topography relief to the shovel-like thrust plane that developed during D3. Our new reconstructed structural evolution concludes that the Gaoligong orocline is an “atypical” orocline.